Bank Credit and Loan Repayment Rates During Covid-19 In Kabale District: A Case of Lyamujungu Sacco - Moses, Agaba; Byamukama Dicky (International Journal of Indonesian Business Review, 2024)
The objective of the study was to investigate the impact of bank credit on loan repayment rates in the Kabale region using Lyamujungu SACCO as the case study. Loan repayment performance at Lyamujungu SACCO has rapidly declined. The loan manager said the situation was getting worse and there was almost no ability to repay the loan. This has to do with the borrower's personality, solvency, and credit history. Members will flee from SACCO if the situation persists. The objectives of the study are:To establish the effect of borrower characteristics on loan repayment during COVID-19 in Lyamujungu SACCO, Examine the impact of borrower's loan solvency on repayment during the COVID-19 pandemic in Lyamujungu SACCO and Determining the effect of borrower's credit term on repayment during the COVID-19 pandemic at Lyamujungu SACCO. This study used a cross-sectional survey method to examine, characterize and compare bank credit and loan repayment in Kabale district, using Lyamujungu SACCO as the case study. The sample size for each subject type was determined using the table of Krejcie and Morgan (1970) cited in Amin (2005). Out of 150 samples, a sample of 108 people was selected for the study. The researcher used both purported sampling and simple random sampling to select members/clients of SACCO. The simple stochastic method is suitable for large numbers like SACCO customers. Based on the results in the table, the null hypothesis for all three variables is rejected, with a significance level of (p = <.000, p = <.040, and p = <.001) for " The average score of the borrower's character during the repayment period", "The average score of the borrower's capacity during the repayment period" and "The average score of the borrower's credit periods during the repayment period debt" respectively. This means that there is evidence that the distribution of mean scores for each of the three variables is not the same depending on the borrower's ability to repay. The study concluded that labor productivity growth decreased and therefore income decreased, investment decreased and affected the borrower's ability to repay loans during the covid-19 pandemic in lyamujungu SACCO. The study recommends that SACCOs conduct a pre-customer assessment before granting a loan and an ongoing review process before and during loan repayment. This way, the bank will be able to know the exact trajectory of the borrower's performance in terms of repayment. This should be reinforced by effective customer relationship management, where the bank acts as more than just a source of credit